2015
DOI: 10.1186/s40623-015-0351-7
|View full text |Cite
|
Sign up to set email alerts
|

Mass eruption rates in pulsating eruptions estimated from video analysis of the gas thrust-buoyancy transition—a case study of the 2010 eruption of Eyjafjallajökull, Iceland

Abstract: The 2010 eruption of Eyjafjallajökull volcano was characterized by pulsating activity. Discrete ash bursts merged at higher altitude and formed a sustained quasi-continuous eruption column. High-resolution near-field videos were recorded on 8-10 May, during the second explosive phase of the eruption, and supplemented by contemporary aerial observations. In the observed period, pulses occurred at intervals of 0.8 to 23.4 s (average, 4.2 s). On the basis of video analysis, the pulse volume and the velocity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 35 publications
3
44
0
Order By: Relevance
“…However, the ash pulses within the footage taken 4, 5 and 6 days later showed an increase in the average initial vertical velocities to 65 m s −1 and-even more prominent-a significant drop of the average pulsation interval t pulse to 4.2 s, coinciding with the significantly increased overall mass flux [13]. Furthermore, these video analyses revealed that two types of explosive pulses could be discriminated by their observed diameter at the vent exit: 'strong' pulses, featuring diameter at a vent of greater than 50 m and 'weaker' pulses, characterised by a diameter at the vent exit of less than 50 m [13]. The two types also significantly differed in their rate of occurrence: the time between weaker pulses (t pulse ) was on average 4.7 s and between strong pulses on average of 37.5 s [13].…”
Section: Insights From Observations: Case Study 1-determination Of Thmentioning
confidence: 89%
See 4 more Smart Citations
“…However, the ash pulses within the footage taken 4, 5 and 6 days later showed an increase in the average initial vertical velocities to 65 m s −1 and-even more prominent-a significant drop of the average pulsation interval t pulse to 4.2 s, coinciding with the significantly increased overall mass flux [13]. Furthermore, these video analyses revealed that two types of explosive pulses could be discriminated by their observed diameter at the vent exit: 'strong' pulses, featuring diameter at a vent of greater than 50 m and 'weaker' pulses, characterised by a diameter at the vent exit of less than 50 m [13]. The two types also significantly differed in their rate of occurrence: the time between weaker pulses (t pulse ) was on average 4.7 s and between strong pulses on average of 37.5 s [13].…”
Section: Insights From Observations: Case Study 1-determination Of Thmentioning
confidence: 89%
“…Measurements made by a thermal camera mounted at a distance of 8.3 km from the vent on 4th May revealed average initial pulse velocities of 45 m s −1 and average pulsation intervals t pulse of ∼20 s (see Table 1 for Notation), meaning that on average three pulses occurred every minute [17]. However, the ash pulses within the footage taken 4, 5 and 6 days later showed an increase in the average initial vertical velocities to 65 m s −1 and-even more prominent-a significant drop of the average pulsation interval t pulse to 4.2 s, coinciding with the significantly increased overall mass flux [13]. Furthermore, these video analyses revealed that two types of explosive pulses could be discriminated by their observed diameter at the vent exit: 'strong' pulses, featuring diameter at a vent of greater than 50 m and 'weaker' pulses, characterised by a diameter at the vent exit of less than 50 m [13].…”
Section: Insights From Observations: Case Study 1-determination Of Thmentioning
confidence: 97%
See 3 more Smart Citations